DAKWAH ISLAM DAN DINAMIKA IDENTITAS SOSIAL MASYARAKAT PESISIR SUMATERA UTARA - Harahap, Nurhanipah; Harahap, Nurhasanah (INSTITUT AGAMA ISLAM NEGERI PONTIANAK, 2025)
This article examines the historical process of the spread of Islam and the dynamics of the formation of social identity in the coastal areas of North Sumatra, with a focus on how Islamic preaching, cultural acculturation, and social interactions shaped the region's distinctive religious and social character. The coastal areas of North Sumatra, including areas such as Barus, Sibolga, and Tapanuli, have held a strategic position as international trade hubs from the 7th century until the colonial period. It was through this trade route that Islam was first introduced by Arab, Persian, and Gujarati traders, which were then disseminated further by Islamic scholars and local figures through a cultural and social preaching approach. This study uses a social and cultural history approach with a descriptive qualitative method, combining literature studies, colonial records, local manuscripts, and interviews with community leaders in the coastal areas. The results show that Islamic preaching in this region did not take place in a confrontational manner, but rather with an accommodative approach that emphasized the integration of Islamic values into the local cultural order. This process resulted in acculturation that is evident in social traditions such as traditional ceremonies, arts, religious language, and the community's moral value system. In this context, Islam serves as a multi-layered source of social identity formation: as a religious, cultural, and social identity closely intertwined with local traditions. During the colonial period, the dynamics of social identity underwent significant shifts with the introduction of Western education systems, colonial bureaucracy, and the flow of modernization. Theoretically, this article asserts that the process of Islamization in coastal North Sumatra cannot be understood simply as the spread of religion, but as a socio-historical process that shapes the construction of collective identity.Keywords: Spread of Islam, Social Identity, Islamization of Coastal North Sumatra[Artikel ini mengkaji proses sejarah penyebaran Islam dan dinamika pembentukan identitas sosial masyarakat di wilayah pesisir Sumatera Utara, dengan fokus pada bagaimana dakwah Islam, akulturasi budaya, dan interaksi sosial membentuk karakter keagamaan an sosial yang khas di kawasan tersebut. Wilayah pesisir Sumatera Utara meliputi daerah seperti Barus, Sibolga, dan Tapanuli memiliki posisi strategis sebagai simpul perdagangan internasional sejak abad ke-7 hingga masa kolonial. Melalui jalur perdagangan inilah Islam pertama kali diperkenalkan oleh para pedagang Arab, Persia, dan Gujarat, yang kemudian disebarluaskan lebih jauh oleh ulama dan tokoh lokal melalui pendekatan dakwah kultural dan sosial. Penelitian ini menggunakan pendekatan sejarah sosial dan kultural dengan metode kualitatif deskriptif, menggabungkan studi literatur, catatan kolonial, naskah lokal, dan wawancara dengan tokoh masyarakat di wilayah pesisir. Hasil penelitian menunjukkan bahwa dakwah Islam di wilayah ini tidak disebarkan secara konfrontatif, melainkan dengan pendekatan akomodatif yang menekankan integrasi nilai-nilai Islam ke dalam tatanan budaya lokal. Proses ini menghasilkan akulturasi yang tampak dalam tradisi sosial seperti upacara adat, kesenian, bahasa keagamaan, dan sistem nilai moral masyarakat. Dalam konteks ini, Islam menjadi sumber pembentukan identitas sosial yang berlapis: sebagai identitas religius, budaya, dan sosial yang terjalin erat dengan tradisi lokal. Pada masa kolonial, dinamika identitas sosial mengalami pergeseran signifikan seiring masuknya sistem pendidikan Barat, birokrasi kolonial, dan arus modernisasi. Secara teoritis, artikel ini menegaskan bahwa proses Islamisasi di pesisir Sumatera Utara tidak dapat dipahami hanya sebagai penyebaran agama, tetapi sebagai proses sosial-historis yang membentuk konstruksi identitas kolektif.]Kata Kunci: Penyebaran Islam, Identitas Sosial, Islamisasi Pesisir Sumatera Utara.